Flaring activity from magnetic reconnection in BL Lacertae. Issue 1 (9th March 2023) - Agarwal, S; Banerjee, B; Shukla, A; Roy, J; Acharya, S; Vaidya, B; Chitnis, V R; Wagner, S M; Mannheim, K; Branchesi, M
ABSTRACT: The evolution of the spectral energy distribution during flares constrains models of particle acceleration in blazar jets. The archetypical blazar BL Lacertae provided a unique opportunity to study spectral variations during an extended strong flaring episode from 2020 to 2021. During its brightest γ-ray state, the observed flux (0.1–300 GeV) reached up to $2.15\, × \, 10^{-5}\, \rm {ph\, cm^{-2}\, s^{-1}}$, with sub-hour-scale variability. The synchrotron hump extended into the X-ray regime showing a minute-scale flare with an associated peak shift of inverse-Compton hump in γ-rays. In shock acceleration models, a high Doppler factor value >100 is required to explain the observed rapid variability, change of state, and γ-ray peak shift. Assuming particle acceleration in minijets produced by magnetic reconnection during flares, on the other hand, alleviates the constraint on required bulk Doppler factor. In such jet-in-jet models, observed spectral shift to higher energies (towards TeV regime) and simultaneous rapid variability arises from the accidental alignment of a magnetic plasmoid with the direction of the line of sight. We infer a magnetic field of ∼0.6 G in a reconnection region located at the edge of broad-line region (∼0.02 pc). The scenario is further supported by lognormal flux distribution arising from merging of plasmoids in reconnection region.